KURVA SORPSI FOSFAT MENURUT LANGMUIR DAN FREUNDLICH SEBAGAI PENDUGA KEBUTUHAN PUPUK FOSFAT PADA ANDISOLS SUMATERA BARAT - Dian Fiantis (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2004)
Andisols are among the most productive soils in the world, but these soils also strongly retained phosphate. The high capacity for phosphate sorption in Andisols is due to their high content of active Al and Fe compounds. The objectives of this study were to assess the effect of soil properties on P sorption, buffer capacities and requirements of some benchmark soil profiles in Mt. Marapi and Mt. Pasaman. The P sorption characteristics of Andisols from West Sumatra were described using Langmuir and Freundlich equations. The P sorption maximum in Mt. Pasaman soils was higher than in Mt. Marapi soils. The most important soil properties affecting P sorption and buffer capacities were oxalate Si and Fe, Al (Sio Feo and Alo), dithionite Al (Ald), pyrophosphate Al (Alp), which explained 89% of the variance in sorption maxima and 83% of P buffering indices. Allophane, Alo and Ald were positively correlated with P sorption maximum. Contrary to general assumption that organic matter had an inverse relation with P sorption maxima, in this study, however, there was no trend observed between P sorption maxima and organic carbon. Organic C has poor relationship with this parameter. Andisols from Mt. Marapi and Mt. Pasaman need P input between 320 to 7,800 mg P kg-1 to maintain the P level in soil solution at 0.2 mg kg-1.